Assessment of the antibiofilm and antiquorum sensing activities of Eucalyptus globulus essential oil and its main component 1, 8-cineole against methicillin-resistant Staphylococcus aureus strains. (May 2018) - Merghni, Abderrahmen; Noumi, Emira; Hadded, Ons; Dridi, Neyla; Panwar, Harsh; Ceylan, Ozgur; Mastouri, Maha; Snoussi, Mejdi
Abstract: Antibacterial resistance is an increasingly serious threat to global public health. The search for new anti-infection agents from natural resources, with different mode of actions and competitive effects became a necessity. In this study, twenty height methicillin-resistant Staphylococcus aureus (MRSA) strains were investigated for their biofilm formation ability. Subsequently, the antibiofilm effects of Eucalyptus globulus essential oil and its main component 1, 8-cineole, against MRSA, as well as their antiquorum sensing potential, were evaluated. Our results displayed the potent efficacy of both E . globulus essential oil and 1, 8-cineole against the development of biofilms formed by the methicillin-resistant strains. Additionally, E . globulus essential oil showed more potent of anti -QS activity, even at a low concentration, when compared to 1, 8-cineole. All these property of tested agents may pave the way to prevent the development of biofilm formation by MRSA and subsequently the spreading of nosocomial infection. Highlights: Methicillin-resistant Staphylococcus aureus (MRSA) strains were investigated for their biofilm formation ability. Antibacterial properties of the E. globulus EO and the 1, 8-cineole, were investigated against characterized MRSA strains. Tested agents showed an interesting antibacterial, antibiofilm, anti-swarming and anti-quorum sensing activities.